The performance measurement model of mosques in Malaysia based on the maqasid shariah index approach / Muhd Fauzi Abd. Rahman, Nor’azam Mastuki and Sharifah Norzehan Syed Yusof. - Abd. Rahman, Muhd Fauzi; Mastuki, Nor’azam; Syed Yusof, Sharifah Norzehan (Universiti Teknologi MARA Cawangan Selangor, 2016)
There are relatively few studies that have been done with regards to the performance measurement of mosques. Despite the perceived uniqueness of mosques as non-profit organisations, this paper shows that the adoption of performance measurement model from the private sectors can also be applied in the case of faith-based non-profits organisations. The survey covered the whole of Malaysia. Given the size of the population and the large geographical area to be covered, a self-administered questionnaire was used as the main method of data collection. Structure Equation Model (SEM) was performed to analyse the data. The results show that there are significant relationships between the four main variables which are resources, processes, outputs and Maqasid Shariah Index which form the basis of performance measurement modelling. The findings from this study indicate that mosques in general, are not effective in meeting their Shariah objectives especially the one related to the objective of “preserving religion”.